2010
DOI: 10.1186/1747-597x-5-6
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the relationship between parental attitudes and behaviour and young people's consumption of alcohol

Abstract: BackgroundConcern is growing regarding frequent and excessive misuse of alcohol by young people. The average age at which young people in Europe start to drink is twelve and a half, and during the last decade, the quantity of alcohol consumed by younger adolescents in the UK has increased. Families are known to play an important role in shaping young people's alcohol misuse, although family risk and protective factors associated with misuse in a UK context are in need of further investigation.MethodsThe study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
3
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 42 publications
7
54
3
8
Order By: Relevance
“…However, whereas previous studies have shown that parenting style (53) and parenting skills (54, 55) are related to the child’s propensity to engage in socially non-normative and illegal behaviors including substance use (10, 21, 56, 57), the present study demonstrates the importance of affective bonding during the developmental period proximal to adolescence, when opportunities for substance use initiation markedly increase.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…However, whereas previous studies have shown that parenting style (53) and parenting skills (54, 55) are related to the child’s propensity to engage in socially non-normative and illegal behaviors including substance use (10, 21, 56, 57), the present study demonstrates the importance of affective bonding during the developmental period proximal to adolescence, when opportunities for substance use initiation markedly increase.…”
Section: Discussioncontrasting
confidence: 91%
“…Toward this goal, it is well known that deficient parenting skills (8), inconsistent and conflictual communication (9, 10), low supervision (11) and punitive discipline (12) amplify risk for initiating SU and subsequently developing SUD (13). In addition, neglectful parenting augments risk for these outcomes (14).…”
Section: Introductionmentioning
confidence: 99%
“…The authors of several studies indicate that the older children are, the higher chance there is for them to drink alcohol (13,20 (23)(24)(25). In our respondents, these aspects of parental control were confirmed to be very important as well, otherwise the chance to drink alcohol increased 2.5 times (95% CI=1.84-3.41).…”
Section: Discussionsupporting
confidence: 48%
“…The results of another study point to the fact that if siblings drank alcohol, there was a significantly increased chance of respondent's alcohol abuse (24). In our study group, if respondents had siblings who drank alcohol every day, there was a chance of their alcohol abuse 4.37 times higher (95% CI=1.78-10.69).…”
Section: Discussionmentioning
confidence: 42%
“…In addition, recent data have highlight the existence of protective factors, such as parental control and a supportive environment [104,105]. Studies have consistently found that the parenting style significantly protects against adolescent drinking behavior.…”
Section: Environment and Heritability Factorsmentioning
confidence: 99%